APPLICATION OF THE ‘VISUALIZATION’ METHOD IN FOSTERING ORAL COMMUNICATION AND AUDITORY COMPREHENSION SKILLS AMONG VISUALLY IMPAIRED STUDENTS (GRADES 8–10) (SCIENCE TIME JOURNAL, 2025)
this study investigates the effectiveness of the ‘Visualization’ method in developing oral communication and auditory comprehension skills of visually impaired students in grades 8–10. Using a mixed-method approach, the research evaluates improvements in language performance, engagement, and self-expression. Findings demonstrate that visualization-based strategies enhance linguistic interaction, listening comprehension, and speaking fluency, providing an adaptable framework for inclusive language education